A World in Crisis? / Geographical Perspectives - Johnston J. R; Taylor J. P (Basil Blackwell, 1989)
The Geographical Perspectives of a World in Crisis show the interlinking nature of global, regional and local problems and, further, that these are not uniquely economic, ecological, political or social, but all these and more. Preface, Introduction: A World in Crisis?, The Geography of International Economic Disorder, Draining the World of Energy, Food Production and Distribution and Hunger, The Use of Natural Resources in Developing and Developed Countries, Malthus and Marx and Population Crises, World Capitalism and the Destruction of Regional Cultures, The Individual and the World-Economy, The Question of National Congruence, The New Geopolitics: The Dynamics of Geopolitical Disorder, World-Power Competition and Local Conflicts in the Third World, The World-Systems Project, Epilogue: Our Planet is Big Enough for Peace but Too Small for War, List of Contributors, Index.